Literature Study: Application Of Character Education In The Formation Of Social Attitudes Nationality Of Students Through Social Studies Learning - Wiwik Maladerita; Syafri Anwar; Erianjoni (CV. AFDIFAL MAJU BERKAH, 2023)
Character education is necessary to form an attitude, personality and morals of a nation. in the application of character education can be applied through the learning process, one of which is in the learning of Social Sciences. This study aims to determine the role of Social Science Learning in the formation of students ' character and to determine the application or implementation of character education in social science learning. This research method uses the literature researcher method, literature review research by looking for reference theories that are relevant to the case or problem found . The results of this study are educators or teachers and schools play an important role in shaping the character of students through school rules, activities followed and in the learning process. Character education is applied to students through social science learning adapted to the material and conditions of students. Learning methods and teachers ' understanding of the material also affect the development of character education. In Social Science Learning also has the same purpose as character education, namely to create good citizens and have moral values.